(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث في دراسة وتحليل دور تقييم المدققين الداخليين لأنشطة الرقابة الداخلية في تحسين فعاليتها في الشركات المدرجة في سوق دمشق للأوراق المالية، والأنشطة التي يمارسونها. لتحقيق أهداف البحث تم إعداد استبانة وزعت على عينة من المدققين الداخليين ضمن الشركات المدرجة في سوق دمشق للأوراق المالية بمعدل (56) استبانة استرد منها(42) استبانة، وقد تضمنت الاستبانة الأنشطة التي يمكن أن يقيمها المدققون الداخليون في نظم الرقابة الداخلية والتي تسهم في تحسين فعالية الرقابة الداخلية في الشركات محل الدراسة. ولتحليل البيانات تم استخدام البرنامج الإحصائي SPSS. وتوصل البحث إلى مجموعة من النتائج أهمها: هناك مجموعة من الأنشطة التي يُقيمًها المدققون الداخليون تسهم في تحسين فعالية نظام وأنشطة الرقابة الداخلية، كما أنه لا توجد فروق ذات دلالة إحصائية بين آراء عينة البحث حول دور تقييم التدقيق الداخلي لأنشطة الرقابة الداخلية في تحسين فعاليتها في الشركات المدرجة في سوق دمشق للأوراق المالية. The main of this research is to study and analyze the role of internal auditors’ evaluation of internal control Activities in improving its effectiveness of Listed Companies in Damascus Security Exchange (DSE), and the activities they undertake to achieve this goal. In order to achieve the research’s objectives, a questionnaire was prepared and distributed to a sample of internal auditors working within companies listed in the Damascus Securities Market at the rate of (56) questionnaires. (42) questionnaires of them were regained. The questionnaire included the activities that internal auditors may evaluate in the control Activities and contribute to improving the effectiveness of internal controls in companies. The statistical software SPSS was used to analyze the data. The study concluded that there are a range of activities evaluated by internal auditors in the control activities that improve the effectiveness. In addition to this ,the research concluded that there were no statistic differences between sample’s point of view about the role of the internal audit’s evaluation of internal control activities in improving its effectiveness of Listed Companies in Damascus Security Exchange.